Antibody persistence and immunologic memory in children vaccinated with 4 doses of pneumococcal conjugate vaccines: Results from 2 long-term follow-up studies. Issue 3 (4th March 2017) - Wysocki, Jacek; Brzostek, Jerzy; Konior, Ryszard; Panzer, Falko G.; François, Nancy A.; Ravula, Sudheer M.; Kolhe, Devayani A.; Song, Yue; Dieussaert, Ilse; Schuerman, Lode; Borys, Dorota
ABSTRACT: To investigate long-term antibody persistence following the administration of the 10-valent pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV), we present results of 2 follow-up studies assessing antibody persistence following 2 3+1 schedules up to 4 (NCT00624819 – Study A) and 5 years (NCT00891176 – Study B) post-booster vaccination. In Study A, antibody persistence was measured one, 2 and 4 years post-booster in children previously primed and boosted with PHiD-CV, or primed with the 7-valent pneumococcal conjugate vaccine (7vCRM) and boosted with either PHiD-CV or 7vCRM. In Study B, PHiD-CV was co-administered with meningococcal vaccines, and pneumococcal antibody persistence was measured 2, 3 and 5 years post-booster. An age-matched control group, unvaccinated against Streptococcus pneumoniae, was enrolled in Study A, allowing assessment of immunologic memory by administration of one dose of PHiD-CV to both primed (4 years post-booster) and unprimed 6-year-old children. Four years post-booster (Study A), antibody concentrations and opsonophagocytic activity (OPA) titers remained higher compared to the pre-booster timepoint, with no major differences between the 3 primed groups. Antibody persistence was also observed in Study B, with minimal differences between groups. The additional PHiD-CV dose administered 4 years post-booster in Study A elicited more robust immune responses in primed children than in unprimed children. Long-term serotype-specific antibody persistence and robust immunologic memory responses observed in these 2 studies suggest induction of long-term protection against pneumococcal disease after PHiD-CV vaccination.